2021
DOI: 10.1111/jth.15425
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on activity assay discrepancies in factor VIII and factor IX products

Abstract: Coagulation factor VIII (FVIII) and factor IX (FIX) play pivotal roles in hemostasis, and their congenital deficiency leads to the Xlinked bleeding disorders hemophilia A and B, respectively. These conditions are managed by prophylactic and on-demand regimens using plasma-derived or recombinant FVIII and FIX products. 1 Both regimens are based on the observation that the severity of bleeding and associated arthropathy are directly related to the factor levels of the individual. 2 The goal of prophylaxis is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Early studies reported the OC/CS assay ratio as ~0.9 for rFVIII-Fc activity measurements [94,95], whereas in subsequent studies, it was as low as ~0.5 for some reagents combinations and some patients' plasma samples [96][97][98]. Similar OC/CS ratios were found for other BDD-FVIII-based variants: turoctocog alfa, simoctog alpha, and moroctocog alfa [87,97]. This indicates that all BDD-FVIII variants may show such discrepancy, though particular assay setups may minimize it.…”
Section: Efmoroctocog Alfamentioning
confidence: 66%
See 2 more Smart Citations
“…Early studies reported the OC/CS assay ratio as ~0.9 for rFVIII-Fc activity measurements [94,95], whereas in subsequent studies, it was as low as ~0.5 for some reagents combinations and some patients' plasma samples [96][97][98]. Similar OC/CS ratios were found for other BDD-FVIII-based variants: turoctocog alfa, simoctog alpha, and moroctocog alfa [87,97]. This indicates that all BDD-FVIII variants may show such discrepancy, though particular assay setups may minimize it.…”
Section: Efmoroctocog Alfamentioning
confidence: 66%
“…For the wild-type full-length (FL) rFVIII, tested versus purified pdFVIII standard, the OC and CS assays generally produce similar results, whereas these may be discrepant for a modified FVIII. In particular, deletion of the B-domain may result in lower value of FVIII activity measured by OC assay up to ~0.5-fold of the CS assay result [86,87]. The OC/CS assay discrepancy causes an uncertainty in FVIII potency assignment; thus, selection of appropriate method for that should be supported by a clinical study.…”
Section: Discrepancy In Activity Measurements Of Modified Fviii Variantsmentioning
confidence: 99%
See 1 more Smart Citation